2005
DOI: 10.1002/cphc.200400335
|View full text |Cite
|
Sign up to set email alerts
|

What are the Implications of Nonequilibrium in the O+OH and O+HO2 Reactions?

Abstract: Vibrationally excited O2, OH, and HO2 species have been suggested (J. Phys. Chem. A 2004, 108, 758) to provide clues for explaining the “ozone deficit problem” and “HOx dilemma” in the middle atmosphere under conditions of local thermodynamic disequilibrium (LTD), but the question arises of how much LTD will affect the title ozone sink reactions. Besides providing novel kinetic results, it is shown that LTD tends to disfavor ozone depletion relative to traditional atmospheric modeling under Boltzmann equilibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 89 publications
2
25
0
Order By: Relevance
“…The calculations employed the QCT method and the popular double many-body potential energy surface (Pastrana et al, 1990) (DMBE IV) for HO 2 ( 2 A ). The DMBE IV form is an ab initio based potential function that has been extensively employed in studies of the O + OH reaction and its reverse, using both quantum (Lin et al, 2006) and classical (Varandas, 2005b) methods. Indeed, special care has been taken to achieve a realistic description of the atomdiatom long-range forces, through the inclusion of dispersion and electrostatic energy components.…”
Section: The O + Oh(v) Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…The calculations employed the QCT method and the popular double many-body potential energy surface (Pastrana et al, 1990) (DMBE IV) for HO 2 ( 2 A ). The DMBE IV form is an ab initio based potential function that has been extensively employed in studies of the O + OH reaction and its reverse, using both quantum (Lin et al, 2006) and classical (Varandas, 2005b) methods. Indeed, special care has been taken to achieve a realistic description of the atomdiatom long-range forces, through the inclusion of dispersion and electrostatic energy components.…”
Section: The O + Oh(v) Reactionmentioning
confidence: 99%
“…For example, although it has been noted (AdlerGolden, 1997) that the reaction O + HO 2 could be a potential candidate, previous work (Kaye, 1988) has shown that it is unlikely to play a crucial role in studies of the high atmosphere. Although this assumption is possibly valid for HO 2 in the ground vibrational state as the dynamics only yields OH(v ≤ 6), the argument no longer holds if non-LTE is considered, since up to OH(v = 15) products can then be formed (Silveira et al, 2004;Varandas, 2005b). In addition, the reaction of OH + O 3 has been shown to yield HO 2 vibrationally excited above the classical asymptote for dissociation, and thus can be another potential source of OH(v ) Zhang and Varandas, 2001).…”
Section: Kinetics Mechanism and Input Datamentioning
confidence: 99%
See 3 more Smart Citations